Exploring perceptions of help-seeking for mental health care among young adults in Maputo, Mozambique - Nair, Kartheyani (Department of Social Development, 2023)
The aim of this research was to gain an understanding of the general perceptions, barriers, and facilitators to seeking mental health care among young adults in Maputo, Mozambique. In the context of the pandemic, semi-structured interviews were conducted using the voice note feature on the mobile application WhatsApp. Participants were recruited using purposive and snowball sampling, with the initial participants originating from a social media-led mental health organisation based in the city. The participants' ages ranged from nineteen to thirty and all identified as female. The study employed a phenomenological approach and used theoretical models such as the Behavioural Model of Health Service Utilisation and the Social Identity Perspective to conceptualise and analyse the data. In comparison to studies of mental health help-seeking both globally and in low to middle-income countries, the participants shared similar perceptions surrounding perceived attitudinal and structural barriers and facilitators to seeking mental health care. Participants provided accounts of the different attitudinal barriers such as stigma, societal norms, and perceptions of care. Perceived structural barriers included the availability and affordability of care, with the latter pertaining to private services. Although barriers such as stigma and cultural and religious norms did not directly affect most participants, the importance of addressing them in the broader public was acknowledged. Facilitating factors for seeking care, such as social support, financial alternatives, and access to information proved to assist help-seekers in their search for care. The benefits of the internet and social media as sources of information and network were outlined. From this research, it was concluded that multiple aspects of the help-seeking process may be improved to increase better outcomes for those who need care. Increasing public mental health literacy in a socio-culturally sensitive manner, standardising care, and creating more mental health services in clinics and places of employment or education may contribute to the ease of people's journey to look after their mental health.